International Legal Consolidation of General Principles of Law - Yusuvalieva Rakhima Yusupovna (International Journal of Law And Criminology, 2025)
The general principles of law recognized by civilized nations constitute a foundational source of international law, codified in Article 38(1)(c) of the Statute of the International Court of Justice (ICJ). Their significance lies in bridging gaps in treaty and customary law, thereby ensuring coherence and stability in the international legal order. This article provides an extensive examination of the international legal consolidation of general principles of law, addressing their historical roots, doctrinal interpretations, judicial applications, and codification efforts within the framework of international organizations. The study explores the ways in which such principles operate as a source of authority, how courts and tribunals deploy them in practice, and the challenges of universal recognition in a pluralistic legal order. Furthermore, the article engages in a comparative evaluation of recent codification efforts by the International Law Commission (ILC) (2023), and examines debates on the future role of general principles in the evolving landscape of international governance, human rights, and global economic regulation. The findings demonstrate that consolidation of these principles is indispensable for legitimizing international law, addressing fragmentation, and advancing common values in the global legal system.